In vitro sensitivity of Alternaria solani to conventional fungicides and a biofungicide based on tea tree essential oil (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
A study of in vitro sensitivity of five Alternaria solani isolates to cooper-oxychloride,chlorothalonil, difenoconazole, pyraclostrobin and a biofungicide based on tea treeessential oil was carried out. The isolates were obtained from infected tomato leavescollected from five different locations in Serbia. The tested isolates showed the highestsensitivity to pyraclostrobin with EC50 values ranging from 0.0014 to 0.0041 μg ml-1. The EC50 values of difenoconazole were 0.018-0.037 μg ml-1, chlorothalonil 2.99-4.54 μg ml-1, and cooper-oxychloride 13.27-15.63 μg ml-1. All tested A. solani isolates were the least sensitive to tea tree oil (1323.97-3307.08 μg l-1).
Keywords: Alternaria solani; Fungicides; Sensitivity